The Influence of the Independent Teaching Platform on Teachers' Ability In Managing The Pancasila Student Profile Strengthening Project (P5) - Putriana; Edi Waluyo (BELIA Early Childhood Education Papers, 2024)
Simultaneously with the independent curriculum, the Ministry of Education and Culture launched an independent teaching platform. The aim of the independent teaching platform is to help teachers get references, inspiration and insight for implementing the independent curriculum. It is hoped that the independent teaching platform can help teachers understand the implementation of the independent curriculum and the project to strengthen the Pancasila student profile in order to foster teacher creativity and innovation in managing P5 in learning. Therefore, the aim of this research is to find out whether the Merdeka Mengajar Platform (PMM) has an influence on the Management of the Project for Strengthening the Pancasila Student Profile (P5), and how big the influence is. This research uses a quantitative approach, with the help of regression analysis. The population in this study were kindergarten teachers who used the Merdeka Mengajar Platform (PMM) with a sample of 96 teachers. Research data was taken by distributing questionnaires. Then, the research results were processed using normality tests, nonparametric tests, regression analysis, and coefficient of determination. Based on research results, the Merdeka Mengajar Platform (PMM) has an influence on the Management of the Project for Strengthening the Profile of Pancasila Students (P5) in Ngaliyan District. This research also produces an R Square value of 0.473 or 47.3%, so that the Platform Merdeka Mengajar (PMM) variable influences the Project Management variable Strengthening Pancasila Student Profiles (P5) by 47.3% in the moderate category and 52.7% is influenced by factors. Therefore, efforts are needed from teachers to consistently maximize the use of the Merdeka Mengajar Platform (PMM) so that the management of the Pancasila Student Profile Strengthening (P5) Project can also improve.